2020
DOI: 10.3390/ani10101733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ensiling Oxytropis glabra with Whole-Plant Corn at Different Proportions on Fermentation Quality, Alkaloid Swainsonine Content, and Lactic Acid Bacteria Populations

Abstract: Oxytropis glabra (OG) is a leguminous forage that is potentially valuable for solving the shortage of feed for livestock production, while, in large quantities, it may be toxic because of its swainsonine (SW) content. In this study, OG was ensiled with whole-plant corn (Zea mays L.) at 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, and 0:10 ratios on a fresh matter basis, and, after 60 d of ensiling, the chemical composition, fermentation characteristic, SW removal rate, lactic acid bacteria (LAB) populations, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Traditional control measures for such toxic plants include manual removal, herbicides, competitive planting, and biological control, along with preventative measures like medicated feeds, vaccinations, and enhanced pasture management [43]. Additionally, Tao et al [44] discovered that ensiling O. glabra with whole corn in certain proportions reduces its toxic component levels, making it suitable for ruminant feed. Understanding the suitable habitats for toxic plants and how climate change affects their distribution, and visualizing these aspects, are crucial for managing, utilizing, and controlling these plants in pasture management strategies, such as selecting pasture locations, deploying preventive medications and vaccines, and establishing silage feed production bases and control strategies.…”
Section: Research Significance and Limitationsmentioning
confidence: 99%
“…Traditional control measures for such toxic plants include manual removal, herbicides, competitive planting, and biological control, along with preventative measures like medicated feeds, vaccinations, and enhanced pasture management [43]. Additionally, Tao et al [44] discovered that ensiling O. glabra with whole corn in certain proportions reduces its toxic component levels, making it suitable for ruminant feed. Understanding the suitable habitats for toxic plants and how climate change affects their distribution, and visualizing these aspects, are crucial for managing, utilizing, and controlling these plants in pasture management strategies, such as selecting pasture locations, deploying preventive medications and vaccines, and establishing silage feed production bases and control strategies.…”
Section: Research Significance and Limitationsmentioning
confidence: 99%
“…The PSM quantified in both types of silage assessed in the current study were reduced to acceptable levels for feeding ruminants (Tables 1-3), which is in line with former reports [e.g., tannins: 4.86-18.50 g/kg DM [13,54]; phytic acid: 2.85-5.81 g/kg DM [55]; L-dopa: 11-16 g/kg DM [43], L-canavanine: 7.5 g/kg DM [56]]. Likewise, other investigations under other experimental conditions have shown the potential of good silage as a method to reduce TI [53,57], saponins [12], swainsonine [58] and cyanogenic glycoside [59].…”
Section: Effect Of Ensiling Process On the Psm Concentrationsmentioning
confidence: 99%
“…As such, the external microbial inoculant which was added at the start of the ensiling process could have also contributed to the PSM disappearance in the current study. Furthermore, Tao et al [58] reported that all of the most representative strains of Lactobacillus were able to reduce the swainsonine content, a PSM present in a mixed silage of corn with Oxytropis glabra.…”
Section: Effect Of Ensiling Process On the Psm Concentrationsmentioning
confidence: 99%
“…Ensiling is a cost-effective and eco-friendly strategy for large-scale and long-term preservation of wet biomass (Tao et al 2020 ). The combination of anaerobic conditions and acidity protects the biomass from the proliferation of deleterious bacteria and fungi (Yang et al 2001 ), which can enhance the storage duration of biomass with minimum nutrient losses and improve palatability as feed.…”
Section: Introductionmentioning
confidence: 99%